Application of Pentuple Bottom Line (PBL) as a Learning Model in Business Feasibility and Business Sustainability Study in SMEs Griya Madukara Malang City - Mala, Iva Khoiril; Pratikto, Heri; Winarno, Agung; Hidayat, Rachmad; Anam, Hoirul; Sutantri (Fakultas Ekonomi Universitas Kadiri, 2025)
This study aims to assess the business feasibility of Griya Madukara MSME from an environmental perspective, emphasizing how its practices contribute to both ecological and social sustainability. The research employed a descriptive qualitative approach, utilizing in-depth interviews, direct observation, and documentation. A total of 12 informants were involved, including the business owner, seven employees from different divisions, two regular customers, and two local community members participating in ecoprint training. The findings show that Griya Madukara adopts zero-waste principles, uses natural materials in its production, and converts organic waste into compost. Additionally, community involvement and empowerment are central to its sustainability strategy. The business aligns with the Pentuple Bottom Line framework (People, Planet, Profit, Phenotechnology, and Prophet), making it a viable and sustainable community-based MSME model.